English Class: Optimalisasi Kemampuan Billingual Anak-Anak Desa Adat Tenganan Pegringsingan - Santati, Parama; Lakilaki, Eogenie (Penerbit Goodwood, 2024)
Purpose: The purpose of this service is to improve the English language skills of elementary and junior high school students of Tenganan Pegringsingan Traditional Village. Methodology/approach: This service was carried out in Tenganan Pegringsingan Village for two days, with 25 students participating. The methods used were lecture, practice, and making mini pocket dictionary. Evaluation was carried out by assessing English language skills and assessing participants' work using an assessment sheet. Results/findings: Based on the results of the implementation, English Class and Mini Pocket Dictionary assessment states that participants have sufficient English language skills with an average score of 71 which indicates a